The Efficacy of Group Play Therapy on the Social Skills of Pre-School Hearing-Impaired Children - Gita Movallali; Seyyedeh Somayyeh Jalil-Abkenar; Mohammad A'shouri (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: The purpose of the present study was to investigate of the efficacy of group play therapy on the social skills of pre-school hearing-impaired children. Materials & Methods: The present research was a semi-experimental study with pre-test, post-test design and control group. The participants were 30 male hearing-impaired children from pre-schools centers in Varamin and Gharchak provinces using an available method. Subjects were randomly divided into experimental and control groups, each group consisting of 15 children. The experimental group received 12 sessions of group play therapy and the control group did not. The instruments were done using the Raven coloure progressive matrices test and social skills rating scale. The data were recorded and statistically analyzed using MANCOVA. Results: The results of MANCOVA showed that group play therapy had a significant effect on the social skills of hearing-impaired children (P<0.001). The results also revealed that group play therapy had a positive and significant effect on all subscales of social skills in these children: cooperation, self-assertiveness and self-control (P<0.001). Conclusion: Group play therapy can improve the social skills of hearing-impaired children. It is recommended that planning play therapy for hearing-impaired children receives serious attention .